BOOK REVIEW: Joachim G. Persoon, "Spirituality, Power and Revolution: Contemporary Monasticism in Communist Ethiopia" / Vaclav Jezek, "Overview of the Orthodox Church During Communism", Volos Academy of Theological Studies, Volos, 2014, 545 p. - MORARIU, Maxim (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
In 2014, in special circumstances, the Volos Theological Academy in Greece, published a book written by two authors about the relationships between the Orthodox Church and Communism. The first part of it (p. 11-259), signed by the English researcher Joachim G. Persoon, specialised in the history of the Ethiopian Church (he gained his PhD at the School of Oriental and African Studies from the University of London), is in fact the PhD thesis of the first author. Divided in six chapters, the book comprises a series of introductory elements (pp. 11-50) like the literature used by the author in the process of documentation (pp. 15-17), theoretical concepts (pp. 22-29, aesthetical aspects (pp. 30-39), and terminology (p. 39), a big exploration of the history of the monastic life from the area (pp. 51-117) and the most important aspects that defined this life during Darg’s Communist period. The author presents the main geographic aspects and shows how they influenced the development of the monastic life in the area, talks about the importance of the sacred dance for the Ethiopian religion and culture and about the importance of the rules in Ethiopian monasticism and about the importance of the abbeys in the process of evangelism, and presents some examples of important monasteries, chosen from the almost 1000 (p. 14) existing on that territory.